Sepsis in cirrhosis: report on the 7th meeting of the International Ascites Club - Florence Wong (2005)
Sepsis is a systemic inflammatory response to the presence of infection, mediated via the production of many cytokines, including tumour necrosis factor a (TNF-a), interleukin (IL)-6, and IL-1, which cause changes in the circulation and in the coagulation cascade.There is stagnation of blood flow and poor oxygenation, subclinical coagulopathy with elevated D-dimers, and increased production of superoxide from nitric oxide synthase.All of these changes favour endothelial apoptosis and necrosis as well as increased oxidant stress.Reduced levels of activated protein C, which is normally anti-inflammatory and antiapoptotic, can lead to further tissue injury.Cirrhotic patients are particularly susceptible to bacterial infections because of increased bacterial translocation, possibly related to liver dysfunction and reduced reticuloendothelial function.Sepsis ensues when there is overactivation of pathways involved in the development of the sepsis syndrome, associated with complications such as renal failure, encephalopathy, gastrointestinal bleed, and shock with decreased survival.Thus the treating physician needs to be vigilant in diagnosing and treating bacterial infections in cirrhosis early, in order to prevent the development and downward spiral of the sepsis syndrome.Recent advances in management strategies of infections in cirrhosis have helped to improve the prognosis of these patients.These include the use of prophylactic antibiotics in patients with gastrointestinal bleed to prevent infection and the use of albumin in patients with spontaneous bacterial peritonitis to reduce the incidence of renal impairment.The use of antibiotics has to be judicious, as their indiscriminate use can lead to antibiotic resistance with potentially disastrous consequences.c Baseline reduced polymorphonuclear count due to hypersplenism c Baseline elevated heart rate because of the hyperdynamic circulatory syndrome c Baseline hyperventilation due to hepatic encephalopathy c Blunted elevation of body temperature that is often observed in cirrhotic patients 719 SEPSIS IN CIRRHOSIS www.gutjnl.com